Entomofauna associated with a silvopastoral system of Tithonia diversifolia cv. ICA Cuba oc-10, intended for bull fattening - Valenciaga, Nurys; Iraola, J.; Herrera, Magaly; Ruiz, T. E. (Cuban Journal of Agricultural Science, 2024)
To evaluate the entomofauna associated with a silvopastoral system (SSP) of tithonia and improved and natural grasses, intended for bull fattening, an experiment was conducted for four years. A sample of 20 raids was taken during three climatic moments (January, May and September), with the use of the entomological net for each plant component. Results showed the superiority of Insecta class. An amount of 14 orders, 37 families and 76 morphospecies were collected. Out of them, 38 phytophages, 13 visitors, 22 bioregulators, 2 hematophages and 1 omnivore. The most common phytophages were the leafhoppers: Empoasca sp., Hortensia similis, Draeculacephala cubana and a complex of chrysomelids of Epitrix, Diabrotica, Colaspis, Diachus, Typophorus, Cryptocephalus, Oedionychus and Anysostena genera, which provoke their damage with greater emphasis on base grass and on the control area. However, they only reached the category of frequent. The rest were included in the category of infrequent (<10). September was the most representative month of the associated entomofauna. It is concluded that the study of the entomofauna in the evaluated areas confirms the function of the tree component in the agroecosystem. Regarding the SSP with tithonia and base grass, it is demonstrated that the system manages to maintain phytophagous, visitor and bioregulatory species in biological balance, without causing economic damage to the associated plant components. Therefore, it is recommended to maintain phytosanitary surveillance in these areas, by promoting increasingly diverse systems, in order to contribute to the comprehensive management of the agroecosystem.